Natural gas in the Russian economy: the current state and the use - E. Z. Shorov (Вестник Северо-Кавказского федерального университета)
The article discusses the concept and composition of natural gas, its significance, localization, production and consumption in regional economic systems on the territory of the Russian Federation. The role of the gas industry in national economy is presented, the classification of natural gas applications and possible forms of its use as a final product is presented, the problems of optimal strategy planning and tactics for the development of the entire Russian gas complex are actualized. The subject of the study is the current state of the natural gas market, regional aspects of its consumption. In the course of studying the current state and use of natural gas in the Russian economy, we applied theoretical research methods: analysis, synthesis, comparison, generalization. Possible growth points, the development of production infrastructure, logistics and the use of natural gas in the territory of the Russian Federation were discovered. Based on the results of the study, it can be concluded, that scientifically based forecasting of future demand for natural gas, which has consumer value, contributes to more efficient infrastructure planning.